2010
DOI: 10.1161/strokeaha.109.575167
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Cerebral Blood Flow Pressure Autoregulation in Pediatric Patients During Cardiac Surgery

Abstract: Background and Purpose The limits of cerebral blood flow-pressure autoregulation have not been adequately defined for pediatric patients. Mean arterial blood pressure below these limits might contribute to brain injury during cardiac surgery. The purpose of this pilot study was to assess a novel method of determining the lower limits of pressure autoregulation in pediatric patients supported with cardiopulmonary bypass. Methods A prospective, observational pilot study was conducted in children (n=54) undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
131
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(137 citation statements)
references
References 24 publications
3
131
1
2
Order By: Relevance
“…However, we do think these results are representative as the trend of the cerebral oxygenation is more important than the absolute value [19]. There was no continuous registration of all parameters; thus, the relation between blood pressure and rScO 2 as an estimator of autoregulatory ability could not be measured [10,26]. In the future, a prospective, human study is required to confirm the effects of CO 2 -insufflation with 5 mmHg on cerebral oxygenation hemodynamics and with neurodevelopmental follow-up.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, we do think these results are representative as the trend of the cerebral oxygenation is more important than the absolute value [19]. There was no continuous registration of all parameters; thus, the relation between blood pressure and rScO 2 as an estimator of autoregulatory ability could not be measured [10,26]. In the future, a prospective, human study is required to confirm the effects of CO 2 -insufflation with 5 mmHg on cerebral oxygenation hemodynamics and with neurodevelopmental follow-up.…”
Section: Discussionmentioning
confidence: 81%
“…Because a significant decrease in the rScO 2 can be damaging, we gave preference to evaluate the effects of CO 2 -insufflation of up to 10 mmHg in this animal experimental model. Previous research showed that a nadir rScO 2 of less than 35 % [21] is associated with impairments in neurodevelopment [8,10].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cerebral oximetry, a noninvasive optical technology employing NIRS, may allow for real-time determination of the various autoregulatory thresholds 3 and thereby provide relevance as a means to define clinically meaningful hypotension. Cerebral oximetry measures regional cerebral blood (representing approximately 75% venous and 25% arterial content) oxygen saturation (rSO 2 ) using principles similar to conventional pulse oximetry (i.e., Beer-Lambert Law) which allow for the determination of oxygenated and deoxygenated hemoglobin by the differential absorption of various near-infrared light wavelengths.…”
mentioning
confidence: 99%
“…L'oxymétrie cérébrale, une technologie optique non effractive utilisant la NIRS, pourrait permettre de déterminer en temps réel les divers seuils d'autorégulation, 3 ce qui pourrait avoir une pertinence dans la façon de définir une hypotension significative d'un point de vue clinique. À l'aide de principes semblables à ceux de l'oxymétrie de pouls conventionnelle (par ex.…”
unclassified